An Ice Core Slice Scanning Tool based on Line-scan Camera - Jiang Xiao; Yang Qi; Shi Jianguang; Liu Jingbiao; Yu Haibin; An Chunlei (E3S Web of Conferences, 2021)
The ice core from polar ice sheet is one of the most valuable archives of past climate and environment. The ice core visual stratigraphy, based on optical scanning analysis, provides the most intuitive information of the micro-particles and/or air bubbles in the ice. At present, only few labs can perform high quality visual stratigraphy analysis in the world. Here, we develop an ice core slice scanning tool based on line-scan camera. The machine uses the high-resolution characteristics of the line-scan camera to complete high-resolution imaging of the ice core slices through linkage with the linear light sources. A motor drive and control system is developed to complete the uniform scanning control of the line-scan camera and light sources. A special control program and human-computer interaction interface are developed to realize the parameter setting, motor control and imaging result display. The test results show that the proposed ice core slice scanning tool meets the design requirements and its imaging results are significantly better than area-scan cameras under the same conditions.